Pengaruh Variasi Basis Krim Ekstrak Daun Petai Cina (Leucaena Leucocephala) Terhadap Sifat Fisik Sediaan - Parmadi, Anom (Indonesian Journal on Medical Science, 2024)
Chinese petai leaves are known to the public to have properties for treating fresh and swollen wounds by chewing or crushing the leaves and then placing them on the wound. Semi-solid dosage forms such as ointments, creams and gels are an option for better healing because they allow longer drug contact time and protect wounds from external contamination. The development of petai cina leaf extract into a cream dosage form is very important. This research aims to determine whether the ethanol extract of petai cina (Leucaena leucocephala) leaves can be made into a cream preparation and to determine the effect of base variations on the physical test of the cream preparation. This type of research is experimental research with a maceration method using 96% ethanol solvent. The data was processed statistically using the ANOVA test and SPSS 21.0 for windows. The yield of the maceration method was 6.89% w/w. The organoleptic of the cream is blackish green, jasmine aroma, pH 6, homogeneity test is homogeneous, the type of cream was O/A and the cream provides protection. The results of the ANOVA test showed a significance value (p 0.100) › 0.05. This shows that there is no influence of base variations on the adhesion test of each formula. The results of the spreadability ANOVA test show a significance value (p 0.000) ‹ 0.05, which indicates that there was an influence of base variations on the spreadability test.